Pornografi Dan Kekerasan Terhadap Perempuan (Kajian Kritis Pandangan Feminisme Radikal) - Atun Wardatun (Universitas Islam Negeri Mataram, 2006)
Some people presume that feminisms are permissive for pornography due to the fact that many women support pornography as an expression of women’s freedom. By critical reading and analysis of radical feminism point of view on women’s sexuality, this work proves that feminisms are ant pornography. Pornography, since it always puts women as the object, is violence against women, dehumanization, and colonialization of women by the domination of patriarchal society. There is no way for women to minimize—if not to bring to an end— pornography but to start realizing that women are the blamed victims and keep on struggling for gaining equal distribution of power between men and women. Besides, women have to ensure that women are not the only party who have responsibilities for moral degradation of society but at the same time women must be the one as the primary controller for their own body and life.